A post mortem study on estimation of stature from humerus in a North Kerala population - Ajesh , P P; Sujith Sreenivas, C (Journal of Indian Academy of Forensic Medicine, 2021)
The identification of a dead body is required in cases of sudden and unexpected death, fires, explosions, railway or aircraft accidents  and decomposed skeletal remains. Estimation of stature is an important parameter like age, sex, and ancestry in medicolegal and  forensic examinations. Regression formulae derived from the major long bones are considered to be more accurate and highly  correlated. There is a need to derive a regression equation and multiplication factor for estimation of stature from length of humerus in  North Kerala population. The present study was conducted on 160 male and 160 female dead bodies brought for medicolegal autopsy  in the Department of Forensic Medicine, Government Medical College, Kozhikode during the period of January 2012 to November  2012. Body length and humerus measurements of the cadavers were recorded after obtaining permission from institutional ethics  committee. The regression equation derived from the study is that the stature in males is 35.93 + 3.973H cm with SE of 4.598 and  stature in Female is 55.33+ 3.265H cm with a SE of 4.272. The various regression equations from different population are compared  to the present study. Humerus to stature ratio in males found to be 19.459 and 19.389 in females. This ratio is higher than the ones  given in all other studies. The Multiplication Factor obtained for males is 5.14 and females is 5.16, both of which are less than the  what is reported in the available studies on Indian populations.
Keywords: Stature; Humerus; Linear regression; Multiplication factor